Compósito de terra autoadensável ativada alcalinamente para a construção de paredes monolíticas - Araújo, Lucas Giovanni Costa de Araújo e (2022)
The soil as a building material is coming back to the focus of the scientific community due to its low incorporated energy and the growing usage of alkaline activation instead of Portland cement or lime. There are few studies about self-compacting soil matrixes as a building technique. Thus, the present work has the objective to develop a self-compacting soil composite with alkali activation for construction of monolithic walls. After a factorial design study, it was selected the best composition of earth, sand, metakaolin and activation solution for the composite production by the mixture spreading in its fresh state and its compressive strength in the hardened state. It was also made assays for physical characterization, X Ray diffraction (DFX) and infrared spectroscopy, V funnel and compressive and flexural strength. The composite’s compressive strength was 8,12 MPa at 3 days and 9,75 MPa at 28 days. The wall showed shrinkage cracks, which did not directly influence its failure mode, and reached a 3,30 MPa tension. It was also evaluated the addition of fibers trying to mitigate the shrinkage cracks. Finally, the compound showed a nice rheological behavior both in its fresh and hardened states being able to be used on the construction of monolithic walls.